PENGARUH PUPUK ORGANIK AMPAS KELAPA TERHADAP PERTUMBUHAN TANAMAN TOMAT (Lycopersicum Esculentum Mill) - Astuti Nirmalani Mendrofa; Gea, Nonozisokhi; Gea, Karunia (Jurnal Sapta Agrica, 2023)
This study aims to determine the effect of coconut dregs on the growth of tomato plants. This research was conducted in the village of Hiliamaeta, Luahagundre sub – district, South Nias district, from April 20 2022 to May 25 2022. This type of research is quantitative research with a true experimental approach. The research design used was RAL (Completely Randomized Design) which consisted of five treatments (P) with four replications (U). The population of this study is 20 units of tomato plants and 20 units of the sample. This research was conducted by fermenting coconut dregs with a mixture of EM4 to become organic fertilizer. Treatment given with certain doses : P 0 was not given coconut dregs, P 1 (50 grams), P 2 (100 grams), P 3 (150 grams), P 4 (200 grams). Research date were analyzed by normality test, homogeneity test, hypothesis test, and further test (Duncan and LSD). So it can be concluded that H0 is rejected and H a is accepted, which means there is a difference in the growth of tomato plants when given coconut dregs on plants height and number of leaf blades. Researchers suggest that people should be able to use coconut dregs as a natural organic fertilizer for plants because coconut dregs are very easy to obtain, do not incur large costs and contain important subtances fot the growth of tomato plants (Lycopersicum esculentum Mill).